Congenital Complete Heart Block in Young Women - Triwedya Indra Dewi; Giky Karwiky; Rekha Nova Iyos; Mega Febrianora (Faculty of Medicine Universitas Padjadjaran, 2021)
Objectives: To present a rare case of Congenital Complete Heart Block (CCHB) in the setting of post-cesarean delivery of an asymptomatic young patient.Methods: A 30-year-old female patient complained of sudden weakness after C-section delivery with spinal anesthesia. She presented a slow heart rate and Complete Heart Block (CHB) on electrocardiogram (ECG). After one week of observation, the ECG still presented a CHB condition. A permanent pacemaker (PPM) with DDDR mode was then installed for this patient.Result: The etiology of CHB, especially at a young age, is unclear, hence challenging. A patient with a CCHB is difficult to diagnose, especially without any previously related symptoms. This abnormality is usually detected during routine screening not related to cardiovascular disease. The patient in this case study presented an ECG of persistent CHB from the time this patient was admitted until one week after observation. The echocardiography showed normal results. Other modalities to confirm diagnosis and evaluate the prognosis of a CCHB should be done.Conclusion: Establishing the etiology of CHB in young patients is challenging. The implantation of PPM is needed because the condition is permanent, regardless the etiology. However, implanting a permanent pacemaker is not always an easy decision, especially in young patients.